An Evaluation Of Project Manager Performance In The Success Of Agile Scrum-Based Application Development Projects - Permana, Decky; Wahyu Nugraha, Diki; Irawan, Debi (Jurnal ICT : Information and Communication Technologies, 2026)
The role of a Project Manager (PM) is vital to the success of application development projects. Within the Agile Scrum framework, a PM ensures effective team collaboration, adaptability to changing requirements, and the timely completion of sprints. This study aims to evaluate Project Managers' performance in relation to the success of Agile Scrum-based application development projects. Using a quantitative approach a survey was conducted with 20 respondents from Agile-based software development teams. The study reveals that leadership, communication skills, and decision-making are the most significant contributors to project success. These factors collectively account for 78% (R² = 0.78) of the project success rate reported. The TELOS feasibility analysis indicates high feasibility in the technical (90%), operational (85%), and schedule (80%) dimensions, while the economic (75%) and legal (70%) dimensions identified areas for improvement. Ultimately, the performance of the Project Manager plays a dominant role in determining the success of Agile Scrum project implementation.